KEKATOLIKAN SEKOLAH KATOLIK MENURUT PANDANGAN GEREJA - Herman P. Panda (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2019)
In this article the author presents the views of the Catholic Church herself about the identity of Catholic schools. This view is spread in a number of Church documents both issued by the Vatican II and by the Pope and Roman Dicasteries. According to this view, Catholic schools have a basic call to educate children and young people to become individuals who have integrity, wisdom and firm faith. For this reason, every Catholic School must continue to maintain a supernatural vision, a strong anthropological foundation, an integral education, the spirit of unity and togetherness of all those involved in the educational process and sustained by the living testimony of the teachers.